How common is isolated dysphasia among patients with stroke treated with intravenous thrombolysis, and what is their outcome? Results from the SITS-ISTR. Issue 11 (25th November 2015) - Lundström, Erik; Zini, Andrea; Wahlgren, Nils; Ahmed, Niaz
Abstract : Objectives: To describe the frequency and outcome of isolated dysphasia among patients treated with intravenous thrombolysis (IVT). Design: Patients registered in the SITS International Stroke Thrombolysis Register (SITS-ISTR). Participants: Patients with stroke (N=58 293) treated with IVT between December 2002 and December 2012. Setting: A multinational, prospective, observational monitoring register. Main outcome measures: Isolated dysphasia and modified Rankin Scale (mRS). Methods: We identified patients presenting with isolated dysphasia by reviewing items within the baseline National Institutes of Health Stroke Scale (NIHSS). We performed descriptive statistics for baseline and demographic data, and reported patients' characteristics, radiological data and changes in their NIHSS score within 7 days and mRS score at 3 months. We also reported corresponding data from the general SITS-ISTR cohort. Results: We found isolated dysphasia at baseline in 1.14% (663/58 293) of all patients treated with IVT patients. Patients with isolated dysphasia had a longer onset to treatment time, lower proportion of visible infarctions on admission imaging scan and atrial fibrillation, and were less often classified as having large vessels causing strokes, in comparison with the rest of the SITS-ISTR. Symptomatic intracerebral haemorrhage occurred in 2.3% of patients per SITS-MOST definition and fatal outcome in 5.5%. At 7 days, 50% of patients with isolated dysphasia recovered completely and at 3 months, 86.3% patients were functionally independent (mRS score 0–2), 71.7% had an excellent outcome (mRS score 0–1) and 45.5% had an mRS score of 0. Conclusions: A low proportion of patients with isolated dysphasia are treated with IVT. Half of these patients were fully recovered at 7 days.